Stres Kerja pada Karyawan - Nabilah, Nabilah (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
The number of female workers in the current era of globalization who participate in the world of work, it can lead to work stress with the demands of various roles and conflicts that might occur in the work environment. This study aims to determine the influence of organizational climate, role conflict and time management of female workers. The sample in this study were female workers with 212 respondents located in the Cimanggis sub-district of Depok. The sampling technique used in this study is non-probability sampling. The data analysis used in this study is multiple regression analysis at the 0.05 significance level. The results showed that there was a significant influence on organizational climate, role conflict and time management on work stress. The results of the minor hypothesis test indicate that reward, warmth, standards, intra-role conflict, inter-role conflict, goal setting and prioritization and preference for the organization have a significant influence on job involvement.